You Don't Know What You've Got till It's Gone! Unemployment and Intertemporal Changes in Self-Reported Life Satisfaction - Marcus Klemm (Deutsches Institut für Wirtschaftsforschung (DIW), 2011)
This paper uses concurrently and - for the first time - retrospectively reported life satisfaction from the 1984 to 1987 waves of the German Socio-Economic Panel to study the importance of different comparison standards for the empirical correlation of unemployment and subjective life satisfaction. It is found that unemployed individuals do not only report significantly lower concurrent satisfaction, but also recall reduced satisfaction from past unemployment well, and retrospectively upgrade their past satisfaction scores. Therefore, the short-term negative effects of unemployment on individual life satisfaction reported in the literature so far are likely underestimated. At the same time, the empirical findings cast doubts on the usefulness of subjective life satisfaction for the precise quantification of welfare effects because of changing comparison standards which greatly limit the intertemporal comparability of the data. For this reason, such data also appear to be of limited use for monitoring long-term economic or social development.
Keywords: C23; C81; I31; J64; 330; Life satisfaction; well-being; unemployment; longitudinal and retrospective studies; Zufriedenheit; Lebensqualität; Arbeitslosigkeit; Längsschnittanalyse; Deutschland